Meningkatkan Efektivitas Pendidikan Pertanian Melalui Pemanfaatan Teknologi Informasi dan Komunikasi - Hariyadi Hariyadi; Yusrizal Yusrizal (Universitas Palangka Raya, 2023)
The use of Information and Communication Technology (ICT) in agricultural education in developing countries has become very important in improving the quality and productivity of agriculture, as well as addressing the problems faced by farmers in developing countries. The aim of this research is to describe the experience of using ICT in agricultural education in developing countries, as well as to identify the advantages and disadvantages of using ICT. The method used in this study is a literature review by collecting data from various sources such as articles, books, and research reports. The results of the study show that the use of ICT in agricultural education in developing countries has been done in various ways, such as the development of agricultural applications, distance learning, and the use of simulation software. Although there are some obstacles such as limited access and dependence on technology, the use of ICT in agricultural education in developing countries can provide advantages in improving the effectiveness and efficiency of learning, as well as expanding social networks and collaboration among students. However, to optimize the advantages and overcome the limitations of using ICT in agricultural education in developing countries, cooperation between the government, educational institutions, and technology industry is needed in building adequate ICT infrastructure, providing affordable ICT access, as well as providing training and technical support for ICT users in agricultural education.